International standards of rights in the field of social security - Наньєва, Марія Іванівна; Наньєва, М. І.; Nanieva, M. I. (My University, 2023)
International standards of rights in the field of social security are a set of norms established in various international legal acts. These standards define decent living conditions for people, ensure personal development and social security, and have a significant impact on national legislation in the field of social security. The implementation of standards established at the international level in national legislation is a tool for the development of national legislation towards implementing the rule of law, equality, and social justice. Therefore, this article examines international standards of rights in the field of social security and analyzes the direction of their influence on the sources of social security law. The purpose of this work is to study international social standards and their legal characteristics. The research methodology includes various methods such as the dialectical method, the systemic method, the genetic method, the logical method, the structural-functional method, the formal-legal method, and the comparative-legal and sociological-legal methods. The research results indicate that international standards in the field of social security play an important role, as they must be observed as the minimum criteria for the protection of rights in the sphere of social security. The guarantees provided by a number of ILO Conventions and other international legal acts have been thoroughly investigated, and norms in current legislation that contradict international social standards have been identified. It is emphasized that it is necessary to consider these standards and create specific legal mechanisms that will enable the implementation of international norms and principles.
Chanysheva A. International standards of rights in the field of social security / A. Chanysheva, Y. Krasnov , O. Pozharova , O. Potopakhina, M. Nanieva // Amazonia Investiga. - 2023. - Vol. 12. - Is. 6. - С. 77-83. - DOI: https://doi.org/10.34069/AI/2023.65.05.8
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; міжнародні стандарти пра; соціальне забезпечення; соціальні гарантії; євроінтеграція; адаптація законодавства; international standards of rights; social security; social guarantee; European integration; adaptation of legislation